High‐efficiency high step‐up PWM resonant converter. Issue 6 (1st March 2015) - Cai, Yaping; Xu, Jianping; Chen, Zhangyong; Zhou, Xiang
Abstract : A novel high‐efficiency high step‐up pulse‐width modulation (PWM) resonant converter is proposed. It achieves high‐voltage step‐up by connecting the outputs of the boost converter cell and the isolated single‐ended PWM resonant converter cell in series, and high efficiency by zero current switching for the diode on the secondary side of the transformer of the single‐ended PWM resonant converter cell. The boost converter cell in the proposed converter can not only step‐up voltage, but also absorbs the leakage inductor energy during the turn‐off interval of the power switch to improve power conversion efficiency. Experimental results of a 100 W 35 V/200 V prototype are presented to verify the analysis results of the proposed converter.